Local government in Kazakhstan: an attempt to create a national model - Nikolay Yuvitsa (Управление)
With the development of independence, all public institutions, including the Institute of local government, have undergone changes in Kazakhstan. In the preceding period of local control in the Soviet Union, which includes Kazakhstan, was carried out in forms of state control at the local level, the functions of which are realized in the framework of local councils of people’s deputies. Participation of the population in the management of territories and settlements was limited to the delegation of their powers to elected representatives – deputies of rural districts, district, city and regional councils. Elections of people’s deputies were carried out in accordance with the Constitution and the norms of Soviet law, which also reflected the rights and duties of local councils within the political system of the Union state. With the independence of the country within the framework of the national legislation of the Republic of Kazakhstan, the constitutional status was acquired by local self-government. It is being radically reformed on a democratic basis in order to increase the self-organization of the population within the framework of the model of the national structure and political system of society. For this purpose, the bodies of public administration at the local level – akimats, headed by akims of regions, districts (cities), rural settlements. In addit ion, maslikhats were formed as representative bodies elected by the population - at the district (city) and regional levels. These structures, in accordance with the legislation, are partially endowed with the functions of self-government of the territories. At the same time, taking into account the world experience, the Republic is in the process of formation of self-government institutions of the territories. However, it is too early to talk about the effectiveness of the created national model of local self-government and its mechanisms. In reality, the population of Kazakhstan is not yet able to independently and responsibly solve issues of local importance; to monitor the work of local authorities, etc. The context of local governance in Kazakhstan is changing with the change of society under the influence of internal and external factors. These changes are ongoing and create some uncertainty, leading to the modernization of elements of existing institutions of local government. However, in view of the upcoming changes in the future, new challenges of global, regional and national character, it is necessary to move to more effective mechanisms and methods of managing society at different levels of government on a democratic basis.